Integral Indicator for Monitoring the Condition of Lubricating Materials in Tribocouples - Markova, L. V.; Myshkin, N. K.; Makarenko, V. M.; Semenyuk, M. S.; Kong, H.; Hun, H. -G.; Ossia, S. V. (PLEIADES PUBLISHING INC, 2008)
A miniature integral detector is presented that enables in-line monitoring of the lubricating material in trybosystems by measuring and evaluating four diagnostic parameters simultaneously: chemical disintegration, total contamination content in the oil, water content, and temperature. The detector comprises a self-test system, self-tuning controlled by a microcontroller. The diagnostic parameters of the detector and the standard parameters, such as viscosity and general acid number of mineral and synthetic oils, are compared for their analysis. The validity of the detector's output data is confirmed, which assures its broad application for in-line assessment of the performance of the oil and condition of the tribosystem in general given the high information content and the level of computerization.